Reading the Quran Through Semanalysis: Text, Significance, and Intertextual Relations - Mohammad Irfan Farraz Haecal; Abdul Murad (Senarai: Journal of Islamic Heritage and Civilization, 2025)
This study employs the theoretical framework of semanalysis to examine the interpretation of a Qur’anic verse concerning the phenomenon of rain. The research applies a methodological sequence that begins with the semanalytic approach, proceeds through an analysis of the concepts of genotext and phenotext, explores the distinction between signification and signification, and culminates in the investigation of intertextual relations within the text. The findings indicate that the meaning of rain in the Qur’an is dynamic and context-dependent, shaped by the interpreter’s engagement with its social, linguistic, and religious dimensions. Ultimately, rain is represented as both a manifestation of divine mercy and a symbolic admonition, urging humanity to contemplate the transcendence and omnipotence of Allah.